2012
DOI: 10.1542/peds.2011-1624
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Facilitated Substance Use Screening and Brief Advice for Teens in Primary Care: An International Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Primary care settings provide an important venue for early detection of substance use and intervention, but adolescent screening rates need improvement. Screening and brief interventions appear effective in reducing adult problem drinking but evidence for effectiveness among adolescents is needed. WHAT THIS STUDY ADDS:A computer-facilitated system for screening, feedback, and provider brief advice for primary care can increase adolescent receipt of substance use screening across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 54 publications
1
111
0
Order By: Relevance
“…There is a growing body of literature suggesting that screening, brief intervention, and referral to treatment (SBIRT) can be an effective approach to integrating the identification and brief treatment into pediatric primary care settings. [44][45][46] Similarly, a recent systematic meta-analysis found significantly better outcomes across studies for adolescents treated for mental health problems using an integrated medical-behavioral health approach. 47 Such approaches are also consistent with the patientcentered medical home model, which uses a team-based approach to care and frequently integrates behavioral health services into primary care.…”
Section: Discussionmentioning
confidence: 98%
“…There is a growing body of literature suggesting that screening, brief intervention, and referral to treatment (SBIRT) can be an effective approach to integrating the identification and brief treatment into pediatric primary care settings. [44][45][46] Similarly, a recent systematic meta-analysis found significantly better outcomes across studies for adolescents treated for mental health problems using an integrated medical-behavioral health approach. 47 Such approaches are also consistent with the patientcentered medical home model, which uses a team-based approach to care and frequently integrates behavioral health services into primary care.…”
Section: Discussionmentioning
confidence: 98%
“…Motivational interviewing fits well within pediatric health care settings (Erickson et al, 2005) and is considered an evidenced-based, frontline approach to reducing substance use through increased levels of patientcentered care, shared decision making, and improved clini-cian-patient relationships (Anstiss, 2009;Rollnick et al, 2008). Brief interventions targeting cannabis have shown favorable results, with single sessions reducing use among pediatric emergency department patients (Bernstein et al, 2009), and primary care patients using screening and brief advice (Harris et al, 2012). A study that compared computer-delivered brief interventions against therapistdelivered brief interventions found that computer-delivered brief interventions reduced cannabis-related consequences (e.g., interpersonal, financial problems), whereas therapistdelivered brief interventions reduced driving under the influence (Walton et al, 2013).…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…102,103 Another promising area of research is the use of selfadministered computer-facilitated screening tools combined with brief clinician intervention. 104 Internetbased intervention, including smart phone applications and social media, may also have utility in clinical settings and warrant investigation. And lastly, given the significance of nicotine addiction, pharmacotherapy and combination pharmacotherapy deserve additional study in both adolescents and young adults.…”
Section: Research Gapsmentioning
confidence: 99%